(15-x)+6-x=14

Simple and best practice solution for (15-x)+6-x=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15-x)+6-x=14 equation:



(15-x)+6-x=14
We move all terms to the left:
(15-x)+6-x-(14)=0
We add all the numbers together, and all the variables
(-1x+15)-x+6-14=0
We add all the numbers together, and all the variables
-1x+(-1x+15)-8=0
We get rid of parentheses
-1x-1x+15-8=0
We add all the numbers together, and all the variables
-2x+7=0
We move all terms containing x to the left, all other terms to the right
-2x=-7
x=-7/-2
x=3+1/2

See similar equations:

| 34=d/15 | | 11/9x=20 | | -7p-7+5p=-2(p+1)-5 | | 4x+251-2x=180 | | -19+7x=3x-22 | | 7x-2x^2=-13 | | 20h+8.25=40+7.25h | | 3(x+2)-1=2x+3)-7 | | -6y+6=14(2y+3) | | -2(x-1)=6-2x | | 6x+x^2=832 | | 108+19=y-1 | | 3x-2x+7=x+7 | | 2(3x+6)=5x+8 | | 3x-12=3(x—4 | | -4(7x+5)=8(1-3x) | | 2x-5(x+4)=16 | | |5x+20|=15 | | –10d+3=–7 | | -7m+12+8m=-4 | | -x-2=-4x-17 | | 3b+22=7b-22 | | -x+1=-4x-17 | | -x-2=4x-17 | | 9y−2=9y−2 | | (3n-3)(n+2)=54 | | 7(x-3)=15 | | 4^2x-20(4^x)=-64 | | 3(2x-5)-2(x-4)=4(x-4) | | -x+1=4x-17 | | 2(3w-4)=-5(w+2 | | 104=-4(-4k-2) |

Equations solver categories